Ctr9, a Key Component of the Paf1 Complex, Affects Proliferation and Terminal Differentiation in the Developing Drosophila Nervous System - Shahrzad Bahrampour; Stefan Thor (G3: Genes, Genomes, Genetics, 2016)
The Paf1 protein complex (Paf1C) is increasingly recognized as a highly conserved and broadly utilized regulator of a variety of transcriptional processes. These include the promotion of H3K4 and H3K36 trimethylation, H2BK123 ubiquitination, RNA Pol II transcriptional termination, and also RNA-mediated gene silencing. Paf1C contains five canonical protein components, including Paf1 and Ctr9, which are critical for overall complex integrity, as well as Rtf1, Leo1, and Cdc73/Parafibromin(Hrpt2)/Hyrax. In spite of a growing appreciation for the importance of Paf1C from yeast and mammalian studies, there has only been limited work in Drosophila. Here, we provide the first detailed phenotypic study of Ctr9 function in Drosophila. We found that Ctr9 mutants die at late embryogenesis or early larval life, but can be partly rescued by nervous system reexpression of Ctr9. We observed a number of phenotypes in Ctr9 mutants, including increased neuroblast numbers, increased nervous system proliferation, as well as downregulation of many neuropeptide genes. Analysis of cell cycle and regulatory gene expression revealed upregulation of the E2f1 cell cycle factor, as well as changes in Antennapedia and Grainy head expression. We also found reduction of H3K4me3 modification in the embryonic nervous system. Genome-wide transcriptome analysis points to additional downstream genes that may underlie these Ctr9 phenotypes, revealing gene expression changes in Notch pathway target genes, cell cycle genes, and neuropeptide genes. In addition, we find significant effects on the gene expression of metabolic genes. These findings reveal that Ctr9 is an essential gene that is necessary at multiple stages of nervous system development, and provides a starting point for future studies of the Paf1C in Drosophila.